Poly(oligoethylene glycol methacrylate)-based polymer electrolyte for dye sensitized solar cell application - Saladaga, Imee A.
Polymer electrolyte based on poly(oligoethylene glycol methacrylate) (POEGM) was studied and found to be a promising polymer electrolyte for dye sensitized solar cell (DSSC) application. High ionic conductivity of polymer electrolyte improved DSSC photovoltaic performance. Furthermore, the presence of iodine and salt was found to be essential for an efficient electron transport within the cells. Irradiance between 908 and 565 W m-2 showed no significant difference in the efficiency, open-circuit voltage and fill factor of the cells but the increase in light intensity improved the Jsc and current density. Long-term stability of the POEGM polymer was studied by comparing characterization results of the sample in 2013 and 2018. X-ray diffraction patterns reveals that the polymer's crystallinity decreased. Fourier transform infrared spectroscopy spectra shows minor changes on the chemical bonds which indicates minor degradation. Calculating kinetic and thermodynamic parameters from thermogravimetric analysis data using van Krevelen model shows endothermic (△≠H°o > 0), unstable (△≠S° < 0) and non-spontaneous (△≠G° > 0) POEGM decomposition process after the dehydration stage. The results shows that the polymer remains stable after five years under storage conditions. These all signify that POEGM is sufficiently stable to be used as polymer electrolyte for actual electronic applications. The results of this work thus demonstrate that POEGM is a better electrolyte compared to PEG for DSSC application